FEATURES OF THE PRIMARIES PROCEDURE IN MODERN RUSSIA - Petrova, R.I. (Perm Federal Research Centre Journal, 2015)
The article presents a comparative analysis of the institution of primary elections - the primaries - in the U.S. (where it has developed a classic version) and in modern Russia. It concerns the strengths and weaknesses of the Russian primaries. In conclusion the article briefly deals with the possible models of the primaries, the gives the assessment of this procedure as a whole.